Association between antibiotic treatment during pregnancy and infancy and the development of allergic diseases. Issue 4 (5th March 2019) - Metzler, Stefanie; Frei, Remo; Schmaußer‐Hechfellner, Elisabeth; von Mutius, Erika; Pekkanen, Juha; Karvonen, Anne M.; Kirjavainen, Pirkka V.; Dalphin, Jean‐Charles; Divaret‐Chauveau, Amandine; Riedler, Josef; Lauener, Roger; Roduit, Caroline; et al.
Abstract: Background: Allergies are a serious public health issue, and prevalences are rising worldwide. The role of antibiotics in the development of allergies has repeatedly been discussed, as results remain inconsistent. The aim of this study was to investigate the association between pre‐ and post‐natal antibiotic exposure and subsequent development of allergies (atopic dermatitis, food allergy, asthma, atopic sensitization and allergic rhinitis). Methods: A total of 1080 children who participated in a European birth cohort study (PASTURE) were included in this analysis. Data on antibiotic exposure during pregnancy and/or first year of life and allergic diseases were collected by questionnaires from pregnancy up to 6 years of age and analysed by performing logistic regressions. To take into account reverse causation, we included models, where children with diagnosis or symptoms of the respective disease in the first year of life were excluded. Results: Antibiotic exposure in utero was significantly and positively associated with atopic dermatitis and food allergy. The strongest effect was on diseases with onset within the first year of life (for atopic dermatitis: aOR 1.66, 95% CI 1.11‐2.48 and for food allergy: aOR 3.01, 95% CI 1.22‐7.47). Antibiotics in the first year of life were positively associated with atopic dermatitis up to 4 years (aOR 2.73, 95% CI 1.66‐4.49) and also suggested a dose‐response relationship. A tendency was observed with asthma between 3 and 6 years (aOR 1.65, 95% CI 0.95‐2.86). Conclusions: Our findings show positive associations between exposure to antibiotics and allergies, mainly atopic dermatitis and food allergy within the first year of life, after prenatal exposure, and atopic dermatitis and asthma after post‐natal exposure to antibiotics in children born in rural settings. Abstract :